Effect of cellulose nanocrystals on the properties of the photoactive aloe emodin poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) packaging film. Issue 4 (10th May 2022) - Le, Truong D.; Phasupan, Pimonpan; Thu, Vu Thi; Bora, Tanujjal; Nguyen, Loc T.
Abstract: In recent years, there has been increasing interest in photoactive packaging materials, which inactivate bacteria via the photoactivation of light‐sensitive compounds. One of the existing challenges is the reduced stability and efficacy of these materials due to light exposure. In this study, the effect of cellulose nanocrystal (CNC) loading on the antimicrobial, barrier, and mechanical properties of the photoactive poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) (PHBV) packaging film has been investigated. The film (CNC‐AE‐PHBV) is composed of aloe emodin (AE) and PHBV at the ratio of 540.48 µg g −1, and CNC. The weight percentage of CNC loading relative to PHBV is varied from 0.5% to 2.0% (w/w). The results show that CNC mitigates the photodegradation of AE in the polymeric matrix and the highest protection is obtained at 0.5% of CNC loading. CNC also augments the hydrophilicity of CNC‐AE‐PHBV films, indicated by the decrease of water contact angle (78°–71.0°). These effects could have led to the increased retention of photodynamic efficacy against Escherichia coli (~4.5 log cycles) of the CNC‐AE‐PHBV films after repeated light irradiation. Nevertheless, no improvement in the barrier as well as mechanical properties of the films has been observed. The findings evidence the important enhancement effect of CNC on the efficacy of photoactive polymer, which can be further explored for developing future antimicrobial packages. Abstract : Photoactive poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) film was prepared by solvent casting. The incorporation of cellulose nanocrystals into the polymeric matrix greatly enhanced the photostability and antimicrobial efficacy of the material after repeated light irradiation.